Losses from top spoilage in horizontal silos in western Kansas - Dickerson, J.T.; Ashbell, G.; Bolsen, K.K.; Brent, B.E.; Pfaff, L.; Niwa, Y. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The top 3 ft. of silage from each of 30 horizontal silos in western Kansas was sampled at three locations across the width of the silo for 2 consecutive years (1990 and 1991). Ninety-five percent of the silages were either corn or forage sorghum, and only 22 percent of the silos were sealed with polyethylene sheeting. Losses of organic matter (OM) from spoilage were estimated by using ash content as an internal marker. Sealing silos dramatically reduced the estimated spoilage losses in the top 3 ft. All silages had greater estimated spoilage losses in the top 18 in. in 1991 than 1990; sealing reduced spoilage losses of OM at that depth by 16 and 37 percentage units in 1990 and 1991, respectively. Sealing reduced losses in the second 18 in. by 4 percentage units in 1990 and 13 units in 1991. The dry matter (DM) contents were lower in forage sorghum silages than in corn silages, and DM contents of sealed silages were lower than those of unsealed silages in both years. Silage in the top 18 in. had higher pH values than that in the second 18 in.; however, corn silages in the top 18 in. had the highest pH values in 1990, whereas forage sorghum silages had the highest values in 1991.
Keywords: Beef; Survey; Top spoilage; Silage; Bunker; Trench